Diabetes and Hypertension Screening Platform for Sub-District Health Promoting Hospital to Track Community Health - Tawalbeh, Anas; Abdulmana, Sahidan; Langsari, Kholed; Worlee, Anuwat; Niseng, Zakee (Journal of Health Systems Research, 2024)
Background and Rationale: This subproject aimed to develop a digital platform for diabetes and hypertension screening for sub-district health promoting hospital (SHPH) to tract community health to align with efficient community development of the big project. Methodology: This participatory action research involved 3 target areas of 3 SHPHs (Khaotum, Yarang, and Ma’mawi) and 3 sub-district administrative organizations (SAOs: Yarang, Pakoo, and Sakhobon) in Pattani province. The research process began with community survey to analyze the problems of executives in using data for decision-making. The big project offered platforms to executives for monitoring and decision-making. The platform of diabetes and hypertension screening to monitor community health was developed for the present study. Executives were able to access health data for planning and decision-making. The research recruited 39 samples representing 4 groups of stakeholders: 6 SAO executives and employees, 9 executives and nurses of SHPHs, 9 village health volunteers (VHVs), and 15 patients/relatives. The samples were selected purposively (from SOAs and SHPHs) and randomly (VHVs and patients). Questionnaires and interviews were tools for evaluating satisfaction and the platform uses. Results: The development of the digital platform solved data problems with convenient use and high satisfaction to users through serial trainings. Evaluation using questionnaires and interviews found that: 1) the change of community health screening from a manual (paper) based to digital based delivered accurate, fast, convenient, and systematically stored database for real time use. This helped future planning operations on tracking community health. 2) SHPH and SOA could see trends of community health problems at real time and plan to mitigate problems with precision, clarity, and accuracy. 3) The platform served as communication and collaboration medium between SOA, SHPH, VHVs, and target groups. 4) It could facilitate the basic health screening, make an appointment for treatment and follow-up for people in need. Post-training evaluation of platform use skill was at high score. Suggestions: Responsible officers in monitoring community health and service users should receive comprehensive, clear and easy-to-understand training on the use of this new platform.